Influence of the attack angle on the performance of vibratory cultivators - Gheorghita N; Birisi S (Journal of Research and Innovation for Sustainable Society, 2019)
The effect of working tools on agricultural soil, materialized either in displacements or in elastic or plastic deformations of materials, indicates the possibility of using the resonance phenomenon according to their physico-mechanical properties and the degree of variation to one and the same material, resulting also in the possibility of reducing energy consumption. Thus a theoretical study has been carried out to identify the advantages and problems related to one of the most important elements of the oscillatory tillage tools. Finite Element Method was used to analyse three constructive solutions of the same vibratory working tool, for which it was changed their angle of attack for different values of draft force.